2014
DOI: 10.1175/jcli-d-13-00342.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Climate Divisions to Analyze Variations and Trends in Alaska Temperature and Precipitation

Abstract: By extending the record of Alaskan divisional temperature and precipitation back in time, regional variations and trends of temperature and precipitation over 1920-2012 are documented. The use of the divisional framework highlights the greater spatial coherence of temperature variations relative to precipitation variations.The divisional time series of temperature are characterized by large interannual variability superimposed upon low-frequency variability, as well as by an underlying trend. Low-frequency var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
131
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(149 citation statements)
references
References 29 publications
12
131
1
Order By: Relevance
“…To the extent that the outcomes from this study can be compared to prior literature for the region, the streamflow, temperature, and precipitation findings are broadly consistent with earlier teleconnection analyses (e.g., [4,20,61]). Many of the specific hydroclimatic processes inferred, such as higher autumn-winter streamflows or earlier snowmelt freshets under warmer air temperatures, have been widely observed either in this region, or alternatively in other areas of western North America (e.g., [3,22,25,68]).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…To the extent that the outcomes from this study can be compared to prior literature for the region, the streamflow, temperature, and precipitation findings are broadly consistent with earlier teleconnection analyses (e.g., [4,20,61]). Many of the specific hydroclimatic processes inferred, such as higher autumn-winter streamflows or earlier snowmelt freshets under warmer air temperatures, have been widely observed either in this region, or alternatively in other areas of western North America (e.g., [3,22,25,68]).…”
Section: Discussionsupporting
confidence: 78%
“…Teleconnections to such climate modes have, with the possible exception of the Pacific Decadal Oscillation, enjoyed relatively little scrutiny in southeast Alaska and northwest British Columbia in comparison to other areas of western North America and, indeed, even other areas of Alaska and British Columbia. Nonetheless, prior teleconnection analyses within and near this border region (e.g., [4,5,16,20,32,48,61]) provide encouraging signs that this should be a fruitful approach to conceptualizing and characterizing the interannual streamflow variability of transboundary rivers in the area.…”
Section: Introductionmentioning
confidence: 96%
“…Looking specifically at the maritime Arctic, Polyakov et al (2003) determined that a mean temperature increase of 1.2°C had occurred between the years 1875 and 2000. Bieniek et al (2014) found a mean temperature increase of 1.7°C between 1949 and 2012 specifically in Alaska with winter and spring temperatures having the largest increases (Wendler et al 2012). Additionally, temperature increases started in Alaska around 1977 with a high correlation to the Pacific Decadal Oscillation (Hartmann and Wendler 2005).…”
Section: Discussionmentioning
confidence: 87%
“…The river provides livelihood to the residents of the basin in the form of food, transportation, water, firewood, and building supplies. Over the past 60 years in Alaska, Bieniek et al (2014) found a 1.7°C increase in mean annual temperatures. Increased temperature will likely change water chemistry, alter permafrost distribution (Jorgenson et al 2006, Romanovsky et al 2008, Frey and McClelland 2009, increase glacier melt, increase discharge, and alter inputs to the eastern Bering Sea Streigl 2007, Walvoord et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A primary source of uncertainty is the limited availability of meteorological stations in Alaska to form the basis for extrapolation to unmonitored areas [45]. The downscaling of coarse-resolution CMIP5 global circulation models introduces bias, and some deficiencies are known to exist in CMIP5 simulations of northern latitudes, such as incomplete simulation of the effects of aerosols on clouds [1], overestimation of active layer thickness and the permafrost-carbon feedback, and generally poor representation of the pacific decadal oscillation [46].…”
Section: Discussionmentioning
confidence: 99%